CFD investigation of the cold hydrodynamics of a laboratory scale CFB furnace - Vasan, A.Mercy; Prasanna, N.; Vivekanandan, M.; Gopalakrishnan, V. (JOURNAL OF ADVANCES IN CHEMISTRY, 2016)
This investigation presents a computational and experimental study of the flow characteristics of a laboratory scale CFB cold model riser. i) The first part of the work deals with 2D, CFD validation of a literature based CFB riser of circular cross section of 1m height. Simulation results showed good agreement with experimental literature data for radial profiles of volume fraction and particle velocity. ii) The second part is a work on simulation and experimental verification of a CFB riser flow characteristics of a CFB riser of rectangular cross section (400mm x 550mm x2000mm). An experimental run on the test rig was conducted for sand of 300 micron size at a fluidization velocity of 4 m/s and the fluidization behavior was captured on a high speed camera. For simulation, 3D, transient, Euler-ian approach combined with the Kinetic theory of Granular flow and Gidaspow drag model was used to describe the gas–particle behavior. A frame by frame visual comparison of instantaneous volume fraction distribution was made between camera images and 3D simulated profiles. A further graphical comparison between experimental literature data and simulated 3D profiles of volume fraction and particle velocity profiles yielded fairly good results. It was observed that, in spite of non inclusion of turbulence factor in the current 3D simulation, no significant influence was observed in the results